2019
DOI: 10.4103/jfmpc.jfmpc_340_19
|View full text |Cite
|
Sign up to set email alerts
|

Sociodemographic variations in health-related quality of life (HRQOL) among elderly individuals in an urban locality in India

Abstract: Background: Elderly population is growing rapidly in India. To direct public health actions to improve quality of life among elderly, it is important to understand the sociodemographic factors associated with quality of life. The aim of study was to assess health-related quality of life (HRQOL) among urban elderly in a setting of Assam, India, and to examine how HRQOL varied across different sociodemographic groups among the elderly populations. Materials and Methods: A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 20 publications
3
1
0
Order By: Relevance
“…The finding of the study, which is consistent with previous reports from this region, suggests that elderly people of both genders in this region are equally vulnerable to functional disability [ 2 , 17 - 18 ]. In our study, being widowed as opposed to married was associated with greater odds of functional disability after adjustment for age and gender, which is consistent with previous reports [ 2 , 15 , 19 - 20 ]. Mutual support and help between married couples probably influence the positive health outcomes among married couples during older age [ 19 - 20 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The finding of the study, which is consistent with previous reports from this region, suggests that elderly people of both genders in this region are equally vulnerable to functional disability [ 2 , 17 - 18 ]. In our study, being widowed as opposed to married was associated with greater odds of functional disability after adjustment for age and gender, which is consistent with previous reports [ 2 , 15 , 19 - 20 ]. Mutual support and help between married couples probably influence the positive health outcomes among married couples during older age [ 19 - 20 ].…”
Section: Discussionsupporting
confidence: 93%
“…The lowest educated group had the highest and the highest educated group had the lowest prevalence of functional disability. Differences in the level of health awareness and health behaviors among individuals with different levels of educations might explain such educational gradients [ 19 - 20 ]. Furthermore, the opportunity to get a job with better income is likely to be less among illiterates or less educated people, which may adversely influence their health spending to keep them healthy [ 19 - 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…According to Anandacoomarasamy et al . [ 16 ] and Medhi et al .,[ 23 ] obese subjects had significantly lower general health score that it was in line our results. Furthermore, Class 2 obese healthy individuals had significantly lower general health scores compared to Class 1 obese subjects.…”
Section: Discussionsupporting
confidence: 91%
“…Research has demonstrated that the level of education has an influence on the measurement of QOL. [ 6 29 ] Similarly, this study observed higher odds of having good QOL scores among literate elderly individuals residing in rural areas. The study also highlights that elderly individuals with financial independence could overcome various physical and environmental barriers in rural hilly areas, which, in turn, can result in enhanced social and psychological well-being of the elderly.…”
Section: Discussionsupporting
confidence: 63%